Pendampingan Peningkatan Keterampilan Komunikasi Dan E-Commerce Pada Pelaku UMKM “Achi Craft Gallery”Di Kecamatan Kuranji Kota Padang: Enhancing Communication Skills and E-Commerce Capacity through Digital Marketing Assistance for Achi Craft Gallery MSMEs in Padang City - Marta, Revi; Suwandi, Rifki; Havifi, Ilham; Zahra, Anggita Putri; Rosyada, Qania; Ghazi, Sulthan; Eftriani, Viyola; Salsabila, Serly; Giffari, Muhammad Iqbal Al (Jurnal Hilirisasi IPTEKS, 2026)
Digital transformation has become essential for micro, small, and medium enterprises (MSMEs) to enhance their competitiveness, particularly in marketing communications and e-commerce management. This community service program aimed to strengthen the digital capabilities of Achi Craft Gallery, an MSME located in Padang City, Indonesia, through structured mentoring in marketing communications, digital content creation, marketplace management, and financial record-keeping. The program adopted a participatory action research approach, incorporating training sessions, hands-on practice, individualized mentoring, and continuous evaluation. The results demonstrated substantial improvements in participants' digital competencies, including enhanced skills in content creation, social media management, and customer engagement. The MSME successfully produced more professional visual content, developed a more attractive and persuasive marketplace presence, and implemented more effective and responsive customer communication strategies. In addition, the production process became more efficient, while financial record-keeping evolved from an unstructured manual system to a more organized and easily monitored process. These improvements contributed to strengthened marketing performance and a gradual expansion of market reach. The program offers practical implications for enhancing the digital competitiveness of MSMEs while contributing academically through an integrated mentoring model that combines communication strategies and digital technology adoption. Future initiatives should incorporate digital analytics and foster collaboration among MSME communities to support sustainable business development.